Context, Process, and Participant Response in the Implementation of Family Support Programmes in Spain - Sonia Byrne; Silvia López-Larrosa; Juan C. Martín; Enrique Callejas; María L. Máiquez; María J. Rodrigo (Psicología Educativa: Revista de los Psicólogos de la Educación, 2023)

(untitled)
Implementation research addresses how well a programme is conducted when applied in real-world conditions. However, research based on quality standards is still scarce as it requires monitoring context, process, and participant response. This study applies implementation quality standards to 57 Spanish parenting and family support programmes identified in the COST European Family Support Network project, using an ten-component evaluation sheet sheet. Descriptive analyses showed a good implementation level. The latent profile analysis identified four patterns defined by programme setting: profile 1, Social Services/NGO setting (21.1%), profile 2, Health setting (31.6%), profile 3, Multi-setting (14%), and profile 4, Educational setting (33.3%), differing in professional discipline, training, participant response, and professional perception of implementation. Profile memberships were related to programme outcomes, scaling up, and sustainability. Findings illustrate conceptual and practical challenges that researchers and professionals usually encounter during implementation, and the efforts required to deliver programmes effectively in real-world settings in Spain.